An Introductory Synthetic Data Tool - Iori Thomas; Bobby Stuijfzand (International Journal of Population Data Science, 2023)
Objectives Synthetic data reproduces features of a dataset without disclosing sensitive information, allowing researchers to explore data structures and test code without requiring access to real, potentially sensitive, data. We produced a low-fidelity synthetic data generation tool, accompanied by extensive documentation, allowing novice and expert users to produce such data.